2015
DOI: 10.1177/1359105315573439
|View full text |Cite
|
Sign up to set email alerts
|

Boredom proneness and emotion regulation predict emotional eating

Abstract: Emotional eating is considered a risk factor for eating disorders and an important contributor to obesity and its associated health problems. It has been suggested that boredom may be an important contributor to overeating, but has received relatively little attention. A sample of 552 college students was surveyed. Linear regression analyses found that proneness to boredom and difficulties in emotion regulation simultaneously predicted inappropriate eating behavior, including eating in response to boredom, oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 41 publications
(68 reference statements)
8
86
0
8
Order By: Relevance
“…The propensity to eat in response to positive [96•] and negative emotions [97,98] is called 'emotional eating' [99,100]. Laboratory-based research has shown that emotional eating is predictive of increased food intake in young people [101].…”
Section: What Role Does Emotional Eating Have In the Development Of Cmentioning
confidence: 99%
“…The propensity to eat in response to positive [96•] and negative emotions [97,98] is called 'emotional eating' [99,100]. Laboratory-based research has shown that emotional eating is predictive of increased food intake in young people [101].…”
Section: What Role Does Emotional Eating Have In the Development Of Cmentioning
confidence: 99%
“…Other facets of the emotional eating construct are potentially evident from correlates of the unidimensional measures of emotional eating. These include: reduced inhibitory control [19,20]; reduced ability to differentiate internal bodily signals [16,21]; perceived stress [22,23]; intuitive eating [24]; and difficulties in emotion regulation [25,26]. This evidence suggests that interventions should assess such 'correlates' to obtain accurate evaluation of outcomes.…”
mentioning
confidence: 99%
“…O Leisure Boredom ou Tédio no Lazer parece ser um dos achados mais em relação ao uso de substâncias entre adolescentes, ainda que não esteja claro como funciona esta relação (Weybright et al, 2015). O tédio é um fenômeno complexo, descrito como ansiedade, perda de significado e propósito nas atividades, acompanhado por sentimento de insatisfação, irritabilidade, estresse e sensação de aprisionamento (Crockett, Myhre, & Rokke, 2015). Assim, a propensão ao tédio tem sido associada a alguns tipos de transtornos de humor, raiva e agressividade, menor satisfação com o trabalho e com a vida, maior busca de sensações e baixos níveis de autonomia (Spaeth, Weichold, & Silbereisen, 2015).…”
Section: Resultsunclassified